Liquidity and solvency of a company and the rate of return: An analysis of the Warsaw Stock Exchange - Justyna Zalewska; Natalia Nehrebecka (Central European Economic Journal (CEEJ), 2019)
The purpose of the article is to analyse the impact of various financial ratios used to evaluate a company's liquidity and solvency on the rates of return on the shares of companies listed on the Warsaw Stock Exchange. In the context of developing countries, the relationship between liquidity and solvency on the one hand and the return on equity on the other is still not clear. Poland is the most economically developed country in Central and Eastern Europe. A thorough analysis is necessary to take appropriate action and introduce adequate regulations in the country, as well as to create the foundation for researching other economies in this region. In addition, this article includes new estimators that have not yet been taken into account but that may affect the rates of return, which will contribute to the literature on the subject and to the development of knowledge on the volatility of returns on shares. In the study, we have calculated the time-varying beta coefficients of the capital asset pricing model (CAPM) model and analysed portfolios based on three liquidity ratios and four solvency ratios, which were computed using the CAPM, Fama-French and Carhart models. The empirical study described in the article focuses on companies listed on the Warsaw Stock Exchange in the period from 1 January 1999 to 30 June 2013. Regressions were estimated by the least-squares method and by quantile regression. Based on the results, it was found that listed companies at risk of bankruptcy are able to meet their short-term liabilities. Liquidity and solvency measured by financial ratios significantly affect the sensitivity of the rate of return on shares to the risk factors expressed in the CAPM, Fama-French and Carhart models.
Keywords: G12; G32; G33; G35; 330; liquidity; solvency; asset pricing models; CAPM; portfolio analysis